Atrial natriuretic peptide and water and electrolyte transport in the human jejunum. Issue 6 (June 1991) - Brunner, J; Lübcke, R; Barbezat, G O; Yandle, T G; Espiner, E A
Abstract : The effects of atrial natriuretic peptide were investigated on water and electrolyte transport in the human jejunum. Six healthy male volunteers (aged 21-33 years) were studied using a triple lumen perfusion technique. A plasma like electrolyte solution containing polyethylene glycol (5 milligrams) as a non-absorbable marker was perfused into the jejunum at 10 ml/min, and net water and electrolyte transport and transepithelial potential difference were measured. Subjects were studied single blind on two occasions with either intravenous atrial natriuretic peptide (6 pmol/min/kg for 90 minutes) or placebo (saline), both after controlled sodium intake over three days. Plasma atrial natriuretic peptide concentrations rose from (mean (SD)) 10.3 (3.6) pmol/l to a peak of 96.0 (61.8) pmol/l. Jejunal net water and electrolyte fluxes and potential difference were identical in both the atrial natriuretic peptide and the control studies. Compared with placebo atrial natriuretic peptide induced a significantly greater diuresis (peak 10.2 (6.0) v 1.8 (1.0) ml/min, p less than 0.05) and natriuresis (peak 1069 (351) v 376 (208) mumol/min, p less than 0.01) and haemoconcentration (haematocrit 0.405 (0.040) v 0.368 (0.018), p less than 0.01). There was no difference in blood pressure, pulse rate, plasma electrolytes, and plasma osmolality between the two studies. There was no evidence to suggest an effect of atrial natriuretic peptide on jejunal water and electrolyte transport in healthy human subjects.